Understanding visitors' leisure benefits and heritage meaning-making: a case study of Liangzhu Culture Museum. Issue 6 (2nd November 2021) - Zhang, Yingchun; Liu, Huimei
ABSTRACT: This paper aims to extend understanding of visitors' leisure benefits in relation to their meaning-making of heritage through qualitative interviews conducted at Liangzhu Culture Museum (an archaeological world heritage site in Hangzhou, China). Semi-structured interview with 68 museum visitors was conducted to explore their personal, contextual, and interactive interpretations of leisure and heritage meaning-making. The study found four main types of leisure benefits gained from visiting this museum: recreation; learning and education; relationship enhancement; and affection towards the community. It showed that the perceived leisure benefits of some visitors aligned with the museum's officially represented heritage meaning and value; while those of others were intimately linked to their personal memories, collective identities, and sense of place. This study contributes to a better understanding of heritage museum visitation as a leisure activity; visitors' perceptions of the meaning of leisure in the Chinese heritage museum context; and the link between visitors' heritage meaning-making and their leisure experiences.